Sindh Service Delivery Assessment : A Decision-Making Tool for Transforming Funds into Improved Services - World Bank (World Bank, Islamabad, 2017)
Coverage figures also need to be viewed in the context of the grave water quality issues, virtual lack of treatment of sewage and wastewater in a heavily industrialized province, and serious contamination of water bodies and sources. Solid waste collection, which was not covered in detail in this study, is reportedly only 34 percent overall and virtually absent in rural areas, which has impact on the functionality of sanitation infrastructure, and can result in contamination of water bodies. There is no sanitary landfill in the province. Sindh’s lower riparian status exposes it to critical issues of water availability. Pakistan is a highly water stressed country and reduced water flows in the lower Indus have stretched water availability and increased saltwater intrusion. Inadequate drainage has resulted in widespread waterlogging and salinity (with nearly a fifth of the canal command affected). This affects both drinking water and sewerage/drainage systems. The high level of environmental degradation has had serious economic and social consequences. This is compounded by the weak environmental management of a significant urban sector; of about 486 million gallon per day (MGD) of sewage generated by Karachi and Hyderabad alone, a mere 65 MGD is treated, the remaining being discharged raw into water bodies (with reportedly only 1 percent of wastewater treated outside of the two main cities). The study finds that these achievements need to be viewed with considerable caution. Serious structural issues threaten to negate these gains in the immediate future. There is a high dependence on private providers and self-provision where state systems are failing due to growing populations. This remains unregulated, and multiple actors serve as providers with minimal coordination or adherence to standards and regulations. Yet, without the presence of private providers and self-provision, sector performance will be significantly weaker.